ROYA PARSIAL HAK TANGGUNGAN RUMAH SUSUN: PENYELESAIAN KONFLIK NORMA DAN PERLINDUNGAN HUKUM PEMBELI - Sri Sinduwati (Universitas Labuhanbatu, 2026)
The regulation of partial roya in Indonesian legislation reveals a norm conflict between Article 2 paragraph (2) of the Mortgage Law (UUHT), which requires the inclusion of a partial roya agreement in the Deed of Granting Mortgage (APHT), and Article 124 paragraph (2) of the Minister of Agraria/Head of BPN Regulation No. 3 of 1997, which allows partial roya to be carried out without prior agreement in the APHT. This study aims to analyze the regulation of partial roya for apartment units and the form of legal protection for buyers. The research employs a normative juridical method with statutory and conceptual approaches, utilizing the theory of legal hierarchy and the theory of legal protection. The results show that to resolve this norm conflict, the principle of lex superiori derogat legi inferiori is applied, meaning that the higher-ranking provision in the Mortgage Law must prevail. The implementation of partial roya must be agreed upon in advance in the APHT. Legal protection for apartment unit buyers is obtained by including a partial roya clause in the APHT, so that after full payment, the mortgage on the unit can be partially discharged.Keywords: partial roya; apartment unit; mortgage; norm conflict; legal protection